Избранные произведения: в 3 т. (К. Маркс, Ф. Энгельс) - Маркс Карл (1983)
Экземпляры: аб (ретроконверсия) / Инвентарный номер: 7706 / Цена: 1.10 / Сис.шифр: 87.3 / Авт.знак: И 32 / ГРНТИ: 02 / ББК: 87.3